Investigating the Impacts of Millennial and Spiritual Leadership on Organizational Culture and Employee Work Enthusiasm: A Mediation Analysis - Rohmiana, Ismi; Hadi, Syamsul; Subiyanto, Didik (Universitas Gadjah Mada, 2026)
Introduction/Main Objectives: This study aims to investigate how millennial and spiritual leadership impact employee work enthusiasm, particularly examining the role of organizational culture as a mediator in this relationship. Background Problems: Current leadership theories and organizational practices face challenges in addressing the changing needs of Millennials and the principles of spiritual leadership. There is a need for empirical research to demonstrate how these approaches can be woven into the fabric of organizational culture to foster enthusiasm in the workplace. Novelty: The study addresses a gap by examining how organizational culture serves as a mediator between millennial leadership, spiritual leadership, and the enthusiasm of employees in the public sector. Research Methods: Data were gathered using a structured questionnaire from a group of 171 government employees. Path analysis conducted with SmartPLS 4.0 tested both direct and mediating effects. Findings/Results: Millennial leadership does not have a direct impact on work enthusiasm, yet it fosters a positive organizational culture. In contrast, spiritual leadership has a significant effect on both work enthusiasm and organizational culture. The culture within an organization plays a crucial role in shaping how different leadership styles affect employees' enthusiasm for their work. Conclusion: In theory, organizational culture serves as a bridge that connects individual values with those of the organization, fostering an environment where millennial and spiritual leadership can enhance employee work enthusiasm. In practice, organizations should focus on encouraging open communication and recognition as they cultivate these leadership capabilities that promote sustainable enthusiasm.